Post-COVID Mucormycosis: An Emerging Threat in Developing Countries - A Prospective Review - Chakraborty, Debpratim; Adhikary, Sudipa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
COVID-19, with its rapidly mutating strains, poses a significant global health challenge. Recent reports of a surge in mucormycosis cases among COVID-19 patients highlight the urgent need for understanding and addressing this critical complication. This review explores the factors contributing to mucormycosis development in COVID-19 patients and outlines strategies for prevention and management. Several factors, including high glucose levels (diabetes, onset, steroid-induced hyperglycemia), low oxygen levels, elevated iron levels (especially ferritin), metabolic acidosis, and diabetic ketoacidosis, can facilitate the germination of mucor spores. COVID-19 patients with underlying conditions such as diabetes, cancer, or organ transplants are particularly susceptible to mucormycosis due to their immunocompromised state. The growth of the mucor pathogen requires free iron, which is elevated in conditions like diabetic ketoacidosis. This elevated iron level promotes the formation of Cot-H, a crucial component of fungal growth, leading to mucormycosis. Additionally, comorbidities and corticosteroids can suppress the immune system, hindering the body's ability to fight off infections like mucormycosis. Therefore, it is imperative to avoid the indiscriminate use of corticosteroids. Strict control of acute hyperglycemia and comprehensive monitoring of diabetic and immunocompromised COVID-19 patients are essential preventive measures. By addressing these factors, healthcare providers can mitigate the risk of mucormycosis in COVID-19 patients and improve overall outcomes.